Promotion and mitigation of premixed flame propagation in a gaseous-dusty environment with various dust distributions. (April 2019) - Demir, Sinan; Sezer, Hayri; Bush, Torli; Akkerman, V'yacheslav
Abstract: Propagation of a gaseous-dusty premixed flame front in a channel, imitating a methane-air fire scenario in a coalmine, is studied by means of the computational simulations. The core of the computational platform is a finite-volume, Navier-Stokes code solving for the reacting flow equations with a fully-compressible hydrodynamics, transport properties (viscosity, diffusion and heat conduction) and an Arrhenius chemical kinetics. The combustible coal dust particles are incorporated into the solver by means of the Seshadri formulation [Combustion and Flame 89 (1992) 333] such that a real gaseous-dusty environment is replaced by an "effective fluid" with locally-modified, dust-induced flow and flame parameters. The originality of this work is in the consideration of various spatial dust concentration distributions such as homogenous, linear, cubic and parabolic ones. Specifically, flame acceleration due to wall friction is analyzed for all these distributions; the similarity and differences in the evolutions of the flame morphology and velocity in each of these cases as well as in the case of purely gaseous combustion are identified. It is shown that a non-uniform dust distribution may result in an extra distortion or a local stabilization of the flame front, which respectively increases or reduces the total flame surface area, thereby promoting or moderating flame acceleration. Overall, the effects of non-uniform dust distribution become substantial when the channel width exceeds a threshold value proportional to the flame thickness. Highlights: The present study addresses the (fire) safety issues faced in the industries dealing with combustibles such as the coalmining industry. Specifically, premixed combustion in gaseous-dusty environments with non-uniform coal dust concentration distributions is studied. Various dust concentration distributions are considered; similarity and difference in the flame dynamics in each of these cases is identified. It is shown that a non-uniform distribution results in extra distortion/stabilization of the flame, promoting/moderating its acceleration. The analysis is performed by numerical simulations of reacting flow equations with compressible gasdynamics and Arrhenius chemical kinetics.